Squeezed state in the hydrodynamic focusing regime for Escherichia coli bacteria detection - Zhao, Wenhan (2024)
Flow cytometry is an essential technique in single particle analysis and cell sorting for further downstream diagnosis, exhibiting high-throughput and multiplexing capabilities for many biological and biomedical applications. Although many hydrodynamic focusing-based microfluidic cytometers have been demonstrated with reduced size and cost to adapt to point-of-care settings, the operating conditions are not characterized systematically. This study presents the flow transition process in the hydrodynamic focusing mechanism when the flow rate or the Reynolds number increases. The characteristics of flow fields and mass transport were studied under various operating conditions, including flow rates and microchannel heights. A transition from the squeezed focusing state to the over-squeezed anti-focusing state in the hydrodynamic focusing regime was observed when the Reynolds number increased above 30. Parametric studies illustrated that the focusing width increased with the Reynolds number but decreased with the microchannel height in the over-squeezed state. The microfluidic cytometric analyses using microbeads and E. coli show that the recovery rate was maintained by limiting the Reynolds number to 30. The detailed analysis of the flow transition will provide new insight into microfluidic cytometric analyses with a broad range of applications in food safety, water monitoring and healthcare sectors.